Modeling and analysis of a manufacturing cell formation problem with fuzzy mixed-integer programming - TSAI, Chang-Chun (Institutional Knowledge at Singapore Management University, 1997)
Cell formation (CF) has received much attention from academicians and practitioners because of its strategic importance to modern manufacturing practice. In this paper a sophisticated mixed-integer programming (MIP) model is proposed to simultaneously form manufacturing cells and minimize the cost of dealing with exceptional elements. Also, we illustrate how a fuzzy mixed-integer programming (FMIP) approach can be used to solve the CF problem in a fuzzy environment, propose a new fuzzy operator, and examine the impact of different membership functions and operators on computational performance. Our study shows that FMIP not only provides a better and more flexible way of representing the problem domain, it also leads to improved overall performance.